Engineered brain‐targeting exosome for reprogramming immunosuppressive microenvironment of glioblastoma - Jun Yang; Yong Li; Shaoping Jiang; Yuxin Tian; Mengjie Zhang; Shuai Guo; Pengfei Wu; Jianan Li; Lin Xu; Wenpei Li; Yushu Wang; Huile Gao; et al. (Exploration)
Abstract The immunosuppressive microenvironment of glioblastoma multiforme (GBM) severely impacts the response to various treatments, including systemic chemotherapy. Targeted reprogramming of immunosuppressive GBM microenvironment using RNA interference (RNAi) is largely restricted by poor brain delivery efficiency and targeting specificity. Herein, an acid‐cleavable transferrin (Tf) decorated engineering exosome‐based brain‐targeting delivery system (ACTE) was proposed to efficiently deliver small interference RNA towards transform growth factor‐β (siTGF‐β) and doxorubicin (DOX) to GBM site for combination chemo‐immunotherapy. The siTGF‐β and DOX co‐loaded ACTE, termed as DOX&siTGF‐β@ACTE (Ds@ACTE), is designed to specifically recognize the Tf receptor (TfR) on the blood‐brain barrier (BBB). Subsequently, Ds@ACTE undergoes acid‐responsive detachment of Tf within lysosome of brain capillary endothelial cells, leading to the separation of DOX&siTGF‐β@Exo (Ds@Exo) from the Tf‐TfR complex and enhanced BBB transcytosis. After crossing BBB, the separated Ds@Exo can further target GBM cells via the homing effect. In vivo studies validated that Ds@ACTE significantly downregulated the TGF‐β expression to reprogram the immunosuppressive microenvironment, and thereby reinforce the chemotherapeutic effect of DOX and DOX‐induced anti‐tumor immune response. The effectiveness of this strategy not only can provide thinking for designing a more intelligent brain‐targeting system based on engineered exosomes but also explore an effective treatment regimen for GBM.